Interests of Muzaki to Pay Zakat: The Role of Accountability, Transparency, Service Quality, and Financial Technology - Bahri, Efri Syamsul; Putri, Riesya Aulia; Romansyah, Dadang (IQTISHADIA, 2022)
The obligation to pay zakat is regulated in the Qur'an and is a pillar of Islam. Management of zakat is regulated in Law No. 23 of 2011. This study examines the factors that influence the interest of muzaki to pay zakat. This research is a survey of 35 respondents, muzaki in the National Amil Zakat Agency (Baznas). This study uses quantitative methods with purposive sampling. The data were analyzed using partial least square-structural equation modeling (PLS-SEM), which was then processed using the SmartPLS application. Accountability has a positive and significant effect on the interest of muzaki in paying zakat. Transparency, service quality, and fintech have a positive but not significant effect on interest in paying zakat. This study included very little data. Therefore, further research can investigate these factors with an increasing number of samples. Practical implications by considering the antecedents of muzakki's interest in paying zakat, zakat management bodies can improve accountability, transparency, service quality, and fintech in zakat management